Analysis of Japanese Interjection (Kandoushi) In the Tensei Shitara Slime Datta Ken Anime Chapter 1-5 - Tresnasari, Ningrum; Rafif, Naufal Muhamad; Pribadi, Aditya Kresna; Rosiana, Agustina; Akbar, Faizal Muhammad; Jagadhita, Raditya (CENTRAL ASIA AND THE CAUCASUS, 2022)
Interjection, or kandoushi, is a word used to express the speaker's feelings in Japanese. In Indonesia, interjections can also be referred to as “kata seru”. This study describes the types of kandoushi in the Tensei Shitara Slime Datta Ken anime chapter 1-5 and their Indonesian equivalents. The method used in this study is a descriptive method with a qualitative approach. The method used in data collection non participant observation method. Meanwhile, for the analysis, the method used is the referential equivalent method. Based on the results of the research, the kandoushi contained in the Tensei Shitara Slime Datta Ken anime totals 30 data, which is divided into four classifications, including kandoushi kandou counting 12 data, kandoushi yobikake computing 5 data, kandoushi outou summing 10 data, and kandoushi aisatsugo amounting to 3 data. The equivalent meaning in Indonesian that appears in the kandoushi expression in the Tensei Shitara Slime Datta Ken anime depends on when the kandoushi is spoken.